The antecedents of social media adoption: A study on the role of media needs and innovation characteristics / Izzal Asnira Zolkepli - Zolkepli, Izzal Asnira (2014)

(untitled)
In recent years, the popularity of social media has captured considerable attention, especially concerning medium usage and adoption. This phenomenon is seen as a great opportunity for expanding the marketing mix strategy. For this reason, sufficient knowledge of consumer insight is needed to understand the needs and motivations that drive a consumer to adopt social media. Hence, this research is designed to empirically investigate social media needs in relation to social media innovation. Accordingly, the Theory of Reasoned Action, Tri-Component Attitude Model, Theory of Diffusion of Innovation and Theory of Media Uses and Gratifications are reviewed and extended to explain the state of the needs and motivations of consumers together with innovation characteristics in order to identify the antecedents of social media adoption. This research applies a two-phase multi-method strategy; in phase one, the qualitative approach is utilised using six sessions of Focus Group Discussions (FGD) and in phase two, the quantitative approach is utilised using Online Survey Questionnaires. The qualitative research used 48 respondents while for quantitative research, 428 responses were received. In analysing these data, Factor Analysis is employed to discover potential problematic items and to provide a preliminary indication of unidimensionality, discriminant validity and convergent validity. With these results, the Partial Least Squares (PLS) technique is applied to further test the validity of the overall model and the relationships between the variables hypothesized in the model. In testing the mediating effect of social media innovation characteristics, a two-stage process is employed. The structural model is first evaluated without the mediating variables, which is then followed by an evaluation of the structural relationships with mediating variables. From the analysis, it is found that the structural relationship supports the direct effect and indirect effect of the mediator and confirms five out of the seven hypothesised relationships. Overall, the results for the PLS structural model provide statistical evidence that supports the relationship between media needs, innovation characteristics and adoption. The mediating effect of the innovation characteristic that is presumed to enhance the speed of adoption is also supported. Therefore, the findings suggest a set of media needs that consist of personal needs, social needs and tension release needs, which can be used to target and segment the social media users. In addition, the findings suggest that the innovation characteristics of social media do enhance the speed of adoption, which is a good indicator to prove that social media innovativeness plays an important role in the popularity of the social media. The research makes a significant contribution to the theory and academic understanding of the adoption in the area of technology media, specifically in Malaysia, which can be used to guide the marketer to design a better marketing strategy via the social media as a medium of contact and connection.